The Effects of Fine Dust, Ozone, and Nitrogen Dioxide on Health - Ritz, Beate (Dtsch Arztebl Int, 2019)
BACKGROUND: Air pollutants, especially fine dust, ozone, and nitrogen dioxide, pose a danger to health worldwide. In 2005, the World Health Organization (WHO), in order to protect public health, issued global recommendations for maximum levels of fine dust (10 µg/m(3) for fine dust particles smaller than 2.5 µm [PM(2.5)]), ozone, and nitrogen dioxide. The recommended levels are regularly exceeded in many places in Germany. METHODS: This review is based on relevant publications retrieved by a selective search in PubMed and, in part, on an expert statement issued in the name of the International Society for Environmental Epidemiology (ISEE) and the European Respiratory Society (ERS). RESULTS: Air pollutants affect the entire body, from the beginning of intrauterine development all the way to the end of life, causing premature death mainly through lung and heart disease. An epidemiological study has shown, for example, that mortality rises approximately 7% for every incremental long-term exposure to 5 µg/m(3) PM(2.5 )(95% confidence interval: [2; 13]). Aside from lung and heart disease, the carcinogenic effect of fine dust is now well established. High fine-dust exposure has also been linked to metabolic diseases. For example, in a meta-analysis of cohort studies, the incidence of type 2 diabetes mellitus was found to be associated with elevated fine dust concentrations, with a 25% relative risk increase [10; 43] for every 10 µg/m(3) of PM(2.5). More recent studies have shown that these substances cause harm even in concentrations that are below the recommended limits. CONCLUSION: It is very important for public health that the current EU standards for fine dust particles smaller than <2.5 µg are markedly lowered so that health risks can be further reduced, in accordance with the recommendations of the WHO.